2001
DOI: 10.1128/iai.69.12.7941-7945.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Adhesin of Escherichia coli F18 Fimbriae

Abstract: Previous research has suggested that the adhesin encoded by the F18 fimbrial operon in Escherichia coli is either the FedE or FedF protein. In this work, we show that anti-FedF antibodies, unlike anti-FedE serum, were able to inhibit E. coli adhesion to porcine enterocytes. Moreover, specific adhesion to enterocytes was shown with purified FedF-maltose binding protein.The operons of many fimbrial adhesins of Escherichia coli are well characterized (4). They contain genes coding for the major subunit protein, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 13 publications
1
44
0
1
Order By: Relevance
“…In the case of F18 fibrillae, the major subunit FedA is assembled into a helix containing two subunits per turn (123). Minor fimbrial subunits have been implicated in the adherence of F18 fimbriae and AF/R1 fimbriae (48,148,307). However, in the case of F4 and F5 fimbriae, minor subunits are dispensable for adherence (22,303,304), and the major fimbrial subunits (FaeG and FanC) have been implicated in determining the binding activity of their respective adhesins (21,156,250).…”
Section: The -Fimbriae: Flexible Fibrillaementioning
confidence: 99%
See 1 more Smart Citation
“…In the case of F18 fibrillae, the major subunit FedA is assembled into a helix containing two subunits per turn (123). Minor fimbrial subunits have been implicated in the adherence of F18 fimbriae and AF/R1 fimbriae (48,148,307). However, in the case of F4 and F5 fimbriae, minor subunits are dispensable for adherence (22,303,304), and the major fimbrial subunits (FaeG and FanC) have been implicated in determining the binding activity of their respective adhesins (21,156,250).…”
Section: The -Fimbriae: Flexible Fibrillaementioning
confidence: 99%
“…7). The -fimbriae (FUP cluster 6) (367) comprise usher proteins required for the assembly of the F4 fimbrial antigen (K88 fimbriae) (FaeD) (20,22,224,245,315,316,338), the F5 fimbrial antigen (K99 fimbriae) (FanD) (1, 20, 149, 151, 247, [275][276][277]303), and the F18 fimbrial antigen (F107 fimbriae) (FedB) (147,148,307) found in porcine and bovine isolates of enterotoxigenic E. coli (51,362). Furthermore, this group includes adherence factor/rabbit 1 (AF/R1) fimbriae (AfrB) (48), an uncharacterized operon of E. coli (CshB), the locus for diffuse adherence (LdaD) of atypical enteropathogenic E. coli (294), plasmid-encoded fimbriae (PefC) of S. enterica serotype Typhimurium (96,218), and an intestinal colonization factor of rabbit enteropathogenic E. coli (RalD) (2).…”
Section: The -Fimbriae: Flexible Fibrillaementioning
confidence: 99%
“…The functionality of this approach has been recently demonstrated with model systems (9,10,25). Regarding the adhesin of F18 fimbriae, we have shown that E. coli strains carrying this fimbrial type adhere to porcine intestinal epithelial cells via the FedF protein (42). Furthermore, we have recently mapped the receptor binding region of FedF, to be used as a putative surface antigen in lactic acid bacteria (LAB), between amino acid (aa) residues 60 and 109 of FedF (43).…”
mentioning
confidence: 99%
“…Two additional genes from the fed gene cluster, fedE and fedF, have been described as essential for fimbrial adhesion and fimbrial length [11]. However, until now it can not to evaluate F18 adhesive function in regard to either of the two gene products [12].…”
mentioning
confidence: 99%